Face-to-trait inferences in Japanese children and adults based on Caucasian faces - Sakuta, Yuiko (Frontiers in Psychology, 2022)
Recently, many studies have indicated that humans make social evaluations from facial appearances instantaneously and automatically. Furthermore, such judgments play an important role in several social contexts. However, the mechanisms involved in the ability to form impressions from faces are still unknown, as is the extent to which these can be regarded as universal in perceiving impressions. In the current study, computer-generated Caucasian faces were used to assess the universality or cultural differences in impression formation among Japanese children and adults. This study hypothesized that impressions of trustworthiness and dominance may be more fundamental and universal, whereas the impression of competence may be more complex and culture-dependent. In Experiment 1a, 42 children aged 3 to 6 years were presented with 10 pairs of face images and asked which image in each pair was more trustworthy, dominant, or competent. Overall, it was found that as age increased, the rate of agreement of Japanese participants with the judgment of American participants, obtained in a previous study, increased. However, the agreement rate for competence was relatively low. Experiment 1b, conducted with 46 children, was a replication of Experiment 1a, and the results showed the same tendency. In Experiment 2, 45 Japanese adults made impression judgments on 19 pairs of face images identical to those used in Experiment 1b. The results suggested that while dominance was a dimension not easily influenced by developmental changes or culture, trustworthiness could be influenced by cultural differences in facial expression recognition. Therefore, different judgment criteria are used for children and adults. For competence, the agreement rate with Americans was relatively stable and low among the different age groups. This suggests that depending on the dimension of the trait, certain judgments are influenced by cultural context and, therefore, change criteria, while others are based on more universal criteria.